Challenging manifestations of ANCA-associated vasculitis treated with avacopan: two case reports - Chalkia, Aglaia; Politi, Anastasia; Tryfonos, Isavella; Koutsianas, Christos; Gakiopoulou, Harikleia; Vassilopoulos, Dimitrios; Petras, Dimitrios (Frontiers in Immunology, 2025)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a small-vessel vasculitis that frequently affects the kidneys and lungs. Avacopan, a C5a receptor inhibitor, has demonstrated efficacy as a glucocorticoid-sparing therapy, but data on rare or severe manifestations, such as interstitial lung disease (ILD), cardiac involvement, and epididymo-orchitis, remain limited. We report two patients with newly diagnosed AAV and severe kidney involvement requiring hemodialysis. Case 1, a 65-year-old man with MPO-AAV, presented with ILD with a Usual Interstitial Pneumonia (UIP) radiological pattern, cardiac dysfunction, ENT involvement, and peripheral neuropathy. Case 2, a 68-year-old man with PR3-AAV, presented with kidney disease and epididymo-orchitis. Both patients received corticosteroids, rituximab, cyclophosphamide, plasma exchange, and avacopan. Dialysis independence was achieved within the first month in both cases. In Case 1, left ventricular function normalized, and ILD showed radiological improvement over 6 months. In Case 2, epididymo-orchitis resolved completely within 1 month. Both patients achieved clinical remission with minimal glucocorticoid exposure. These cases provide insights supporting the safety and efficacy of avacopan in severe, multisystemic AAV, including rare manifestations, and highlight its potential to promote organ recovery and reduce glucocorticoid-related toxicity in high-risk presentations.